ChemInform Abstract: Efficient Synthesis of 2‐Substituted Phthalimides from Phthalic Acids in One Step. Issue 18 (17th April 2014) - Chorell, Erik; Chorell, Elin
Abstract: This process allows a fast, convenient, and economic access to a wide range of 2‐substituted phthalimides.